First-principles and empirical potential simulation study of intrinsic and carbon-related defects in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Schmidt, Wolf Gero; Rauls, E.; Lindner, Jörg K. N. (physica status solidi (c))
Results of atomistic simulations aimed at understanding precipitation of the highly attractive wide band gap semiconductor material silicon carbide in silicon are presented. The study involves a systematic investigation of intrinsic and carbon-related defects as well as defect combinations and defect migration by both, quantummechanical first-principles as well as empirical potential methods. Comparing formation and activation energies, ground-state structures of defects and defect combinations as well as energetically favorable agglomeration of defects are predicted. Moreover, accurate ab initio calculations unveil limitations of the analytical method based on a Tersoff-like bond order potential. A work-around is proposed in order to subsequently apply the highly efficient technique on large structures not accessible by first-principles methods. The outcome of both types of simulation provides a basic microscopic understanding of defect formation and structural evolution particularly at non-equilibrium conditions strongly deviated from the ground state as commonly found in SiC growth processes. A possible precipitation mechanism, which conforms well to experimental findings and clarifies contradictory views present in the literature is outlined.

Photonic crystal waveguides intersection for resonant quantum dot optical spectroscopy detection - Song, Xiaohong; Declair, Stefan; Meier, Torsten; Zrenner, Artur; Förstner, Jens (Optics Express)
Using a finite-difference time-domain method, we theoretically investigate the optical spectra of crossing perpendicular photonic crystal waveguides with quantum dots embedded in the central rod. The waveguides are designed so that the light mainly propagates along one direction and the cross talk is greatly reduced in the transverse direction. It is shown that when a quantum dot (QD) is resonant with the cavity, strong coupling can be observed via both the transmission and crosstalk spectrum. If the cavity is far off-resonant from the QD, both the cavity mode and the QD signal can be detected in the transverse direction since the laser field is greatly suppressed in this direction. This structure could have strong implications for resonant excitation and in-plane detection of QD optical spectroscopy.
Keywords: tet_topic_phc; tet_topic_qd

Near-field coupling and second-harmonic generation in split-ring resonator arrays - Grynko, Yevgen; Meier, Torsten; Linden, Stefan; Niesler, Fabian B. P.; Wegener, Martin; Förstner, Jens
We simulate the linear and nonlinear optical response from split-ring resonator (SRR) arrays to study collective effects between the constituent SRRs that determine spectral properties of the second harmonic generation (SHG). We apply the Discontinuous Galerkin Time Domain (DGTD) method and the hydrodynamic Maxwell-Vlasov model to calculate the SHG emission. Our model is able to qualitatively reproduce and explain the non-monotonic dependence of the spectral SHG transmission measured experimentally for SRR arrays with different lattice constants
Keywords: tet_topic_meta; tet_topic_shg

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Excitonic Eigenstates of Disordered Semiconductor Quantum Wires: Adaptive Wavelet Computation of Eigenvalues for the Electron-Hole Schrödinger Equation - Meier, Torsten; Mollet, Christian; Kunoth, Angela (Communications in Computational Physics)
A novel adaptive approach to compute the eigenenergies and eigenfunctions of the two-particle (electron-hole) Schrödinger equation including Coulomb attraction is presented. As an example, we analyze the energetically lowest exciton state of a thin one-dimensional semiconductor quantum wire in the presence of disorder which arises from the non-smooth interface between the wire and surrounding material. The eigenvalues of the corresponding Schrödinger equation, i.e., the one-dimensional exciton Wannier equation with disorder, correspond to the energies of excitons in the quantum wire. The wavefunctions, in turn, provide information on the optical properties of the wire. We reformulate the problem of two interacting particles that both can move in one dimension as a stationary eigenvalue problem with two spacial dimensions in an appropriate weak form whose bilinear form is arranged to be symmetric, continuous, and coercive. The disorder of the wire is modelled by adding a potential in the Hamiltonian which is generated by normally distributed random numbers. The numerical solution of this problem is based on adaptive wavelets. Our scheme allows for a convergence proof of the resulting scheme together with complexity estimates. Numerical examples demonstrate the behavior of the smallest eigenvalue, the ground state energies of the exciton, together with the eigenstates depending on the strength and spatial correlation of disorder.

Emilie Du Châtelet and the Transformation of Metaphysics - Hagengruber, Ruth Edith (Emilie Du Châtelet between Leibniz and Newton)

Fachmethodik: Spanisch-Methodik: Handbuch für die Sekundarstufe I und II - Bürgel, Christoph; Sommerfeldt, Kathrin; Steveker, Wolfgang; Vences, Ursula; Wlasak-Feik, Christine (Zeitschrift für Romanische Sprachen und ihre Didaktik)

Technology for Enhancing Statistical Reasoning at the School Level - Biehler, Rolf; Ben-Zvi, Dani; Bakker, Arthur; Makar, Katie (Third International Handbook of Mathematics Education)

Research on the reasoning, teaching and learning of probability and uncertainty - Biehler, Rolf; Pratt, Dave (ZDM)

eFathom – eine Multimediale Einführung in die Werkzeugsoftware Fathom - Hofmann, T.; Biehler, Rolf (Stochastik in der Schule)

Stochastik in der Schule bedankt sich bei Heinz Althoff und Gerhard König - Biehler, Rolf (Stochastik in der Schule)

Probability in Reasoning About Data and Risk. ZDM The International Journal on Mathematics Edu-cation, 44(7)

Weinheim - Priesching, Nicole; Klueting, Edeltraud (Monasticon Carmelitanum. Die Klöster des Karmeliterordens (O.Carm.) in Deutschland von den Anfängen bis zur Gegenwart)

Mystikerinnen des 19. Jahrhunderts – ein neuer Typus? - Priesching, Nicole (Zwischen Himmel und Erde. Körperliche Zeichen der Heiligkeit)

Als Kaiser Franz I. am 27. Oktober 1815 durch Bozen reiste - Priesching, Nicole (Regionale Zivilgesellschaft in Bewegung / Cittadini innanzi tutto. Festschrift für Hans Heiss)

Self-Regulated Learning and Self Assessment in Online Mathematics Bridging Courses - Biehler, Rolf; Fischer, P. R.; Hochmuth, R.; Wassong, Th. (Teaching Mathematics Online: Emergent Technologies and Methodologies)
For providing an overview of our whole bridging-course programme, at first we will discuss our material concerning content-related, didactical, and authoring aspects. Then we will discuss our course scenarios with regard to pedagogical and organisational aspects. Focusing on selected results of an accompanying evaluation study we will finally discuss the acceptance and success of our courses and highlight some interesting findings concerning our learners.

Tutorenschulung als Teil der Lehrinnovation in der Studieneingangsphase „Mathematik im Lehramtsstudium “(LIMA-Projekt) - Biehler, Rolf; Hochmuth, Reinhard; Klemm, Juliane; Schreiber, Stephan; Hänze, Martin (Mathematik lehren in der Hochschule - Didaktische Innovationen für Vorkurse, Übungen und Vorlesungen)

Fachbezogene Qualifizierung von MathematiktutorInnen–Konzeption und erste Erfahrungen im LIMA-Projekt - Biehler, Rolf; Hochmuth, Reinhard; Klemm, Juliane; Schreiber, Stephan; Hänze, Martin (Mathematik lehren in der Hochschule–Didaktische Innovationen für Vorkurse, Übungen und Vorlesungen)

Mathematische Vorkurse neu gedacht: Das Projekt VEMA - Biehler, Rolf; Fischer, Pascal R; Hochmuth, Reinhard; Wassong, Thomas (Mathematik lehren in der Hochschule. Didaktische Innovationen für Vorkurse, Übungen und Vorlesungen)

Training of student teaching assistants and e-learning via math-bridge–Two projects at the German Centre for Higher Mathematics Education - Biehler, Rolf; Hoppenbrock, Axel; Klemm, Juliane; Liebendörfer, Michael; Wassong, Thomas (CETL-MSOR Conference Proceedings 2011)